Bibliometric Study Applied to the Overtopping Wave Energy Converter Device - Paiva, Maycon da Silveira (2020)
The present study aims to analyze the state of the art of scientific studies about the Overtopping device used to convert sea wave energy into electrical energy, by means the Bibliometric methodology. The development of this study took place through the selection of articles from conference proceedings, as well as national and international journals. The Bibliometric methodology consists of a statistical tool that allows quantifying the measurement of production indexes. Using selected keywords, it was conducted a survey of studies in the online databases of Science Direct, SciELO and Google Scholar. The works found then went through a filtering process, in order to limit the Bibliometric study only to studies about Overtopping devices as sea Wave Energy Converter (WEC). Finally, the investigation of these selected articles was carried out under the optics of production and authorship study, content study and study of bibliographic references. Where it was identified growth in publications related to the topic, methodologies used and, among other indicators, the authors most cited in the analyzed articles. The predominant keywords used were “Wave Energy Converter” and “Overtopping”. It was noted that Brazilian universities are leaders in the productivity, presenting more than 36% of the scientific production regarding Overtopping WECs.